2012
DOI: 10.18869/acadpub.aums.1.2.93
|View full text |Cite
|
Sign up to set email alerts
|

Reviewing Sexual Function After Delivery and Its Association with Some of the Demographic Marital Satisfaction Factors

Abstract: BACKGROUND: Desirable sexual function has an important role in strengthening the marital life of the couples. Sexual disorders can cause mental pressure and affect quality of life and marital relationship. METHODS: This was a descriptive analytical study in one group and one phase covering multivariables. The study sample included 384 women after delivery period that had the following inclusion criteria: the age of at least 18 years, delivery in 38-42 pregnancy weeks, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
13
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 15 publications
5
13
1
Order By: Relevance
“…The study findings also showed that demographic factors, including age, education, family income, breast-feeding and parity were associated with women's sexual functioning. These findings are supported by other authors (4,28).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The study findings also showed that demographic factors, including age, education, family income, breast-feeding and parity were associated with women's sexual functioning. These findings are supported by other authors (4,28).…”
Section: Discussionsupporting
confidence: 90%
“…Findings of this study showed that women who had given birth more than six months ago had better sexual functioning in the domains of orgasm, satisfaction and pain. Another study in Iran also showed a significant association between amounts of time passed from delivery and improved sexual functioning scores (28). In our study, multiparous women had better sexual functioning in the domains of desire, orgasm, arousal and satisfaction.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Sexuality is a natural part of life (Boroumandfar et al, 2010) and one of important determinants of quality of life (Botros et al, 2006). When sexual wellbeing is deteriorated, sexual disfunctions appear.…”
Section: Introductionmentioning
confidence: 99%